2021
DOI: 10.1186/s13058-021-01462-3
|View full text |Cite
|
Sign up to set email alerts
|

ESR1 mutation as an emerging clinical biomarker in metastatic hormone receptor-positive breast cancer

Abstract: In metastatic hormone receptor-positive breast cancer, ESR1 mutations are a common cause of acquired resistance to the backbone of therapy, estrogen deprivation by aromatase inhibition. How these mutations affect tumor sensitivity to established and novel therapies are active areas of research. These therapies include estrogen receptor-targeting agents, such as selective estrogen receptor modulators, covalent antagonists, and degraders (including tamoxifen, fulvestrant, and novel agents), and combination thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(161 citation statements)
references
References 84 publications
3
119
0
6
Order By: Relevance
“…Interestingly, the prevalence of BC cells with estrogen receptor 1 (ESR1) mutations is much higher in patients with MBC who received AI (up to 40% versus 1% in MBC patients without prior ET). Despite a clear association between ESR1 mutations and endocrine resistance, data about predicting the response to AI and/or CDK4/6 inhibitors are contradictory [ 48 ]. Further studies are warranted to clarify whether the detection of ESR1 mutations may influence clinical decisions and the indication of CDK4/6 inhibitors in the metastatic or adjuvant setting [ 49 ].…”
Section: Resistance To Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…Interestingly, the prevalence of BC cells with estrogen receptor 1 (ESR1) mutations is much higher in patients with MBC who received AI (up to 40% versus 1% in MBC patients without prior ET). Despite a clear association between ESR1 mutations and endocrine resistance, data about predicting the response to AI and/or CDK4/6 inhibitors are contradictory [ 48 ]. Further studies are warranted to clarify whether the detection of ESR1 mutations may influence clinical decisions and the indication of CDK4/6 inhibitors in the metastatic or adjuvant setting [ 49 ].…”
Section: Resistance To Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…The simplest mechanism by which ESR1 mutations produce resistance is the lifelong constitutive activity that keeps estrogen receptors unaffected by AI depletion of estrogen. In view of this biological mechanism, several retrospective studies have evaluated the interest of selective estrogen receptor modulators (such as tamoxifen) and selective estrogen receptor degraders (such as fulvestrant) with encouraging results [10]. To date, prospective studies are rare but the phase III PADA-1 trial has nevertheless shown that the presence of an ESR1 mutation at baseline leads to a worse prognosis but that the disappearance of the mutation (on cell-free DNA) after 1 month of letrozole + palbociclib improved the prognosis of patients initially positive for ESR1 [11].…”
Section: Paradiso: Is There a Role For Esr1 Mutation Analysis In Breast Cancer?mentioning
confidence: 99%
“…Resistance to endocrine therapy can develop due to mutation or loss of endocrine receptors on tumor cells (e.g., hormone receptor-negative and ESR1 gene mutations) or via the upregulation of pathways independent of endocrine receptors altogether [ 6 , 7 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…ESR1 gene mutations in breast cancer tumor ER are frequently associated with the development of endocrine resistance [ 16 , 17 ]. Mutations in ESR1 can cause activation of ER independent of estrogen levels, allowing for the upregulation of breast cancer cell proliferation in an endocrine therapy-resistant mechanism [ 18 ].…”
Section: Introductionmentioning
confidence: 99%